The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0103-50532000000400016
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and spectroscopic studies of tungstencarbonyl complexes containing nitrogen and phosphorous ligands

Abstract: Este trabalho tratou da síntese, caracterização espectroscópica e do comportamento eletroquímico dos compostos [W(CO) 4 (bipy)] (1), [W(CO) 3 (bipy)(dppm)] (2) e [W(CO) 3 (bipy)(dppf)] (3), bipy = 2,2'-bipiridina; dppm = bis(difenilfosfina)metano; dppf = 1,1'-bis(difenilfosfina)ferroceno. Os dados provenientes das espectroscopias no infravermelho e de RMN 31 P{ 1 H} mostraram que o tungstênio apresenta uma geometria de coordenação octaédrica com as fosfinas atuando como ligantes monodentados. Os estudos eletro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Stability towards oxidation is gained by the presence of the diphosphines. 122 The compound [Mo(CO) 3 (PF 3 ) 3 ] was originally described as occurring only in the mer-form, on the basis of IR spectra. This was an unexpected result, and a reinvestigation using high-field 19 F and 31 P NMR, including computer simulations, has shown that in solution this compound occurs as a mixture of mer-and fac-isomers.…”
Section: Phosphorus- Arsenic-and Antimony-donor Ligandsmentioning
confidence: 99%
“…Stability towards oxidation is gained by the presence of the diphosphines. 122 The compound [Mo(CO) 3 (PF 3 ) 3 ] was originally described as occurring only in the mer-form, on the basis of IR spectra. This was an unexpected result, and a reinvestigation using high-field 19 F and 31 P NMR, including computer simulations, has shown that in solution this compound occurs as a mixture of mer-and fac-isomers.…”
Section: Phosphorus- Arsenic-and Antimony-donor Ligandsmentioning
confidence: 99%